1994
DOI: 10.1111/j.1365-2249.1994.tb06123.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lymphocyte cell death and apoptosis in HIV-2-infected patients

Abstract: SUMMARY Recent evidence suggests that T cell apoptosis could be involved in the pathogenesis of HIV‐1 infection. As the progression of HIV‐2 associated disease appears to be slower than that of HIV‐1, we investigated whether there were differences in the degree of T cell death and apoptosis in peripheral blood mononuclear cell (PBMC) cultures from patients with HIV‐1 or HIV‐2 infection. PBMC from healthy controls (n = 28) and patients infected with HIV‐1 (n = 26: asymptomatic (ASY)/persistent generalized lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…CD4 cell survival is significantly shortened in progressive HIV‐1 infection . Both in vivo and in vitro studies have shown that in HIV‐1 infection rates of apoptosis exceed those in healthy individuals; in HIV‐2 intermediate rates are seen, although with disease progression the proportion of apoptotic cells becomes similar to that observed in HIV‐1 infection . This lower level of apoptosis may explain the relative sparing of T lymphocytes from cell death in HIV‐2 infection.…”
Section: Lessons From Immune Activation and Cellular Kinetics—how Arementioning
confidence: 91%
“…CD4 cell survival is significantly shortened in progressive HIV‐1 infection . Both in vivo and in vitro studies have shown that in HIV‐1 infection rates of apoptosis exceed those in healthy individuals; in HIV‐2 intermediate rates are seen, although with disease progression the proportion of apoptotic cells becomes similar to that observed in HIV‐1 infection . This lower level of apoptosis may explain the relative sparing of T lymphocytes from cell death in HIV‐2 infection.…”
Section: Lessons From Immune Activation and Cellular Kinetics—how Arementioning
confidence: 91%
“…Progression of HIV‐2 infection to AIDS can occur many years after infection and is probably associated with the weakening of the immune system during ageing. In patients who develop AIDS, plasma HIV‐2 levels are comparable to those observed in HIV‐1‐infected AIDS patients, and the symptoms of the disease are undistinguishable [129–131]. The reasons for the difference in disease progression between HIV‐1 and HIV‐2 reside clearly in the different level of viral replication, but why HIV‐2 does not replicate as efficiently as HIV‐1 in humans is not clearly established [130].…”
mentioning
confidence: 99%
“…However, in HIV-2 infection, the proportion of CD4+ T-cells expressing IL-2 is well preserved ( 42 ). HIV-2-infected individuals also possess a higher frequency of CD4+ T-cells capable of expressing both IFNγ and IL-2 in response to Gag-specific peptides than HIV-1 infected individuals ( 72 , 73 ). Further immunological studies revealed the presence of Gag-specific CD4+ T-cells lacking CD57 expression in HIV-2 infection ( 74 , 75 ), indicating better proliferative capacity resulting in higher number of cells in HIV-2 infected individuals ( 75 ).…”
Section: Distinguishing Features Of Cd4+ T-cell Depletion In Hiv-1 Anmentioning
confidence: 99%